First limits from a 3D-vector directional dark matter search with the NEWAGE-0.3b' detector. (29th November 2020) - Yakabe, Ryota; Nakamura, Kiseki; Ikeda, Tomonori; Ito, Hiroshi; Yamaguchi, Yushiro; Taishaku, Ryosuke; Nakazawa, Miki; Ishiura, Hirohisa; Nakamura, Takuma; Shimada, Takuya; Tanimori, Toru; Kubo, Hidetoshi; et al.
Abstract: The first directional dark matter search with three-dimensional tracking with head–tail sensitivity (3D-vector tracking analysis) was performed with a gaseous three-dimensional tracking detector, or the NEWAGE-0.3b' detector. The search was carried out from 2013 July to 2017 August (Run14 to Run18) at the Kamioka underground laboratory. The total livetime is 434.85 d, corresponding to an exposure of 4.51 kg$\>$ d. A 90 % confidence level upper limit on spin-dependent WIMP-proton cross-section of $4.3×10^{2}$ pb for WIMPs with the mass of 150 GeV$\>c^{-2}$ is obtained.